Carbon-supported composite cathode material, preparation method and lithium ion battery

CN116825993BActive Publication Date: 2026-11-03GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310791939.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2026-11-03
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Existing methods for synthesizing cathode materials for lithium cobalt oxide batteries are costly and involve demanding processes, making them difficult to apply in industry. MOFs, as electronic insulators, limit their activity and suffer from insufficient structural stability and lithium-ion kinetics performance.

Method used

A carbon-supported MOFs-LiCoO2 three-dimensional porous composite material was synthesized through in-situ growth and hydrothermal reaction. By utilizing the porous structure of MOFs and the electronic conductivity of carbon nanofibers or graphene, combined with metal doping, a stable composite cathode material was formed, which alleviated the volume expansion of transition metals and improved lithium-ion and electron conduction efficiency.

Benefits of technology

It significantly improves the rate performance and cycle stability of lithium-ion batteries, and the material synthesis process is simple and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116825993B_ABST
    Figure CN116825993B_ABST
Patent Text Reader

Abstract

The application provides a carbon-loaded composite positive electrode material, a preparation method and a lithium ion battery. 1‑X M X O2 / C, wherein M is one or more of aluminum, nickel, niobium, magnesium, lanthanum, zirconium, manganese and molybdenum, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of nanocomposite materials and electrochemical energy storage, specifically to a carbon-supported composite cathode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Lithium-ion battery technology was first commercialized in 1991 and has been widely used in portable consumer electronics, electric vehicles, and energy storage due to its advantages such as high energy density, long cycle life, and good rate performance. Cathode materials are a crucial component of lithium-ion battery materials and have a vital impact on battery performance. Therefore, developing superior cathode materials is essential for the development of lithium-ion batteries.

[0003] Lithium cobalt oxide was the earliest commercially available cathode material for lithium-ion batteries, holding a dominant market share, particularly in consumer electronics. Researchers in both academia and industry have consistently invested heavily in improving the electrochemical performance of lithium cobalt oxide, including modifications such as doping, coating, and structural morphology adjustment, as well as optimizing production processes. One effective strategy is to design lithium cobalt oxide materials into porous nanostructures to improve stability and rate performance. Common methods include chemical vapor deposition, atomic deposition, and template synthesis. However, these methods are costly and have very demanding process requirements, making them difficult to apply in industry.

[0004] Metal-organic frameworks (MOFs) are a type of coordination polymer that has developed rapidly in recent decades. They are mainly composed of central metal building units and multidentate organic ligands interconnected to form a porous three-dimensional network structure. Their main characteristics include large specific surface area, high porosity, low density, simple synthesis methods, tunable structure, and adjustable porosity. However, MOFs are generally electronic insulators, which limits their intrinsic activity. Summary of the Invention

[0005] In view of the problems existing in the prior art, the present invention provides a carbon-supported composite positive electrode material, a preparation method thereof, and a lithium ion battery. In the present invention, a porous / carbon composite nano three-dimensional material with a metal-organic framework (MOFs) structure is synthesized through in-situ growth and hydrothermal reaction. This carbon-supported MOFs-LiCoO2 three-dimensional porous composite material can improve the kinetic performance of lithium ions due to its abundant mesopores. At the same time, MOFs have good flexibility, which can perform confined protection on lithium cobalt oxide particles while effectively relieving the strain caused by volume expansion of transition metals, thus effectively stabilizing the structure. In addition, the excellent electronic conductivity of carbon nanofibers or graphene carbon materials enables efficient conduction of lithium ions and electrons, which greatly improves the rate capability and cycle stability of lithium ion batteries. Moreover, the preparation method of the present invention has simple process and mild conditions.

[0006] The present invention specifically includes the following contents:

[0007] A carbon-supported composite positive electrode material, wherein the carbon-supported composite positive electrode material has a three-dimensional porous structure, and its chemical formula is MOFs-LiCo 1-X M X O2 / C, wherein M is one or more of aluminum, nickel, niobium, magnesium, lanthanum, zirconium, manganese, and molybdenum, and 0<x≤0.1. More preferably, said M is at least one of aluminum, zirconium, manganese, molybdenum, and lanthanum. Specifically, said x may be 0.02, 0.04, 0.06, 0.08, 0.09, 0.1 and the like.

[0008] Preferably, said C is one or more of graphene oxide and carbon fiber.

[0009] A preparation method of a carbon-supported composite positive electrode material, comprising the following steps:

[0010] (1) Mix the first solvent, cobalt source, organic ligand and carbon material, control the molar ratio of cobalt element to organic ligand to be 1.5:(2-5), to obtain a first reaction system; control the first reaction system to carry out a reaction, and perform solid-liquid separation after the reaction is completed, to obtain carbon-supported MOFs, that is, MOFs / C. Specifically, the molar ratio of cobalt element to organic ligand may be 1.5:2, 1.5:2.5, 1.5:3, 1.5:3.5, 1.5:4, 1.5:4.5, 1.5:5 and the like. Specifically, said first solvent may be methanol. Specifically, the solid-liquid separation method may be ordinary filtration, or suction filtration and the like. In the present invention, suction filtration is preferred to ensure efficiency.

[0011] (2) Mix MOFs / C with a lithium source, an additive and a second solvent to obtain a second reaction system; control the second reaction system to carry out a reaction, to obtain the carbon-supported composite positive electrode material, that is, MOFs-LiCo 1-X M XO2 / C. Specifically, the second solvent can be deionized water, wherein M is one or more of aluminum, nickel, niobium, magnesium, lanthanum, zirconium, manganese, and molybdenum, and 0 <x≤0.1。

[0012] Preferably, the preparation method of the first reaction system in step (1) is as follows: First, the cobalt source, organic ligand, and carbon material are dispersed in a first solvent to obtain a cobalt source dispersion system, an organic ligand dispersion system, and a carbon material dispersion system; then, the cobalt source dispersion system, the organic ligand dispersion system, and the carbon material dispersion system are mixed into a homogeneous dispersion system to obtain the first dispersion system. The specific mixing and dispersion method can be ultrasonic dispersion, or electric or manual stirring dispersion; in this invention, ultrasonic dispersion is preferred. Dispersing the cobalt source, organic ligand, and carbon material in the first solvent first, and then mixing them, is more conducive to forming a homogeneous dispersion system, preventing localized uneven mixing, and thus ensuring the uniformity of the composition of the products generated in the subsequent reaction.

[0013] Preferably, in step (1): the cobalt source is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate; the organic ligand is methylimidazole; and the carbon material is one or more of carbon fiber or graphene oxide.

[0014] Preferably, in step (1), the reaction temperature of the first reaction system is 25-35℃ and the reaction time is 4-8h. Specifically, the reaction temperature can be 25℃, 28℃, 30℃, 32℃, 34℃, 35℃, etc., and the reaction time can be 4h, 5h, 6h, 7h, 7.5h, 8h, etc.

[0015] Preferably, in step (2): the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, and lithium nitrate; the additive is one or more of aluminum chloride, nickel sulfate, niobium oxalate, magnesium chloride, lanthanum nitrate, zirconium chloride, and manganese chloride.

[0016] Preferably, in step (2), the molar ratio of lithium to cobalt in MOFs / C in the second reaction system is (1.01-1.05):1; the reaction temperature of the second reaction system is 200-300℃, and the reaction time is 5-10h. Specifically, the molar ratio of lithium to cobalt in MOFs / C can be 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, etc.; the reaction temperature can be 200, 220℃, 240℃, 260℃, 280℃, 300℃, etc., and the reaction time can be 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0017] Preferably, step (2) further includes solid-liquid separation of the second reaction system after the reaction is completed to obtain a wet material; then the wet material is dried in an environment of 90℃-120℃ for 4-12 hours to finally obtain MOFs-LiCo. 1-X M X O2 / C. Specific solid-liquid separation methods include centrifugation and filtration. After separation, it is preferable to wash the wet material at least once with water before drying. The specific drying temperature can be 90℃, 92℃, 95℃, 98℃, 100℃, 105℃, 110℃, 115℃, 120℃, etc., and the drying time can be 4h, 4.5h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, etc.

[0018] A carbon-supported composite cathode material MOFs-LiCo 1-X M X O2 / C lithium-ion batteries, wherein M is one or more of aluminum, nickel, niobium, magnesium, lanthanum, zirconium, manganese, and molybdenum, 0 <x≤0.1。

[0019] Beneficial technical effects of the present invention:

[0020] (1) Metal-organic frameworks (MOFs) possess large specific surface area and high porosity. Using them as lithium-ion cathode materials in this invention is beneficial for improving the kinetic performance of lithium ions during charging and discharging. Simultaneously, MOFs exhibit excellent flexibility, effectively confining and protecting lithium cobalt oxide particles while mitigating strain caused by the volume expansion of transition metals. During the formation of lithium cobalt oxide, the regular atomic arrangement in the MOF structure significantly improves the uniformity and crystallinity of the synthesized lithium cobalt oxide material, further enhancing its electrochemical performance.

[0021] (2) Due to their excellent electronic conductivity, carbon nanofibers or graphene carbon materials are used as the growth matrix for porous MOFs-LiCoO in this invention. A small amount of additives are also added to synthesize carbon-supported MOFs-LiCoO in situ. 1-X M X O2 three-dimensional porous composite materials can achieve high efficiency in lithium-ion and electron conduction, and the materials have good structural stability.

[0022] (3) This invention relates to the fields of nanocomposite materials and electrochemical energy storage. The carbon-supported composite cathode material MOFs-LiCo synthesized in this invention... 1-X M X O2 / C, as a cathode material for lithium-ion batteries, exhibits excellent rate performance and cycle stability. This is because: i) the carbon-supported composite cathode material MOFs-LiCo disclosed in this invention... 1-X M XThe O2 / C MOF structure effectively alleviates the strain problem caused by the volume expansion of the transition metal. At the same time, the metal doping replaces the Co sites in the cathode material, inhibits the change of Co valence state when combined with Co, reduces Co dissolution, and inhibits the release of O, thus stabilizing the bulk structure of the composite cathode material and improving its cycle stability; ii) The composite cathode material disclosed in this invention has a rich mesoporous structure, which is conducive to lithium electron transport and improves the kinetic performance of lithium ions during charging and discharging; iii) The composite cathode material disclosed in this invention is supported by carbon nanofibers or graphene carbon materials with excellent conductivity, which can achieve high efficiency of lithium ion and electron conduction.

[0023] (4) The preparation method of this invention can control the particle size and pore size distribution of the synthesized material by adjusting reaction parameters such as reaction time and reaction temperature, thereby preparing a material that meets the performance requirements. Moreover, the preparation method disclosed in this invention further specifies the specific types and ratios of C, M, organic ligands, and other reaction raw materials, which can improve the reaction efficiency and ensure the stable bonding between the matrix and the composite cathode material. In addition, the process of this invention is simple, the conditions are mild, the raw materials are abundant, and the prepared material has excellent performance, making it suitable for the industrial preparation of high-performance lithium cobalt oxide cathode materials. Attached Figure Description

[0024] Figure 1 This is a schematic diagram illustrating the reaction principle of the method disclosed in this invention;

[0025] Figure 2 MOFs-LiCo synthesized in Example 1 1-X Al X XRD patterns of O2 / CFs;

[0026] Figure 3 TEM image of MOFs-LiCo1-XAlXO2 / CFs synthesized in Example 1;

[0027] Figure 4 MOFs-LiCo 1-X Al X Comparison of electrical properties of O2 / CFs, MOFs-LiCoO2, and LiCoO2. Detailed Implementation

[0028] The technical solution of the present invention will be further explained and illustrated below through embodiments.

[0029] Example 1

[0030] A method for preparing a carbon-supported composite cathode material includes the following steps:

[0031] (1) First, 2g of cobalt nitrate, 25.3g of 2-methylimidazole and 5g of carbon fiber (CFs) (purchased by Aladdin) were ultrasonically dispersed in 15mL of methanol solution. Then, the three solutions after ultrasonic dispersion were mixed, and stirring was turned on at a stirring rate of 35r / min. After reacting for 12h, stirring was turned off and the mixture was allowed to stand for 5min. A purplish-black precipitate was observed. The product was filtered, washed with water and dried in a vacuum oven at 90℃ to obtain carbon fiber loaded MOFs, i.e. MOFs / CFs.

[0032] (2) Take 5g of MOFs / CFs, 6.28g of lithium carbonate, and 0.05g of aluminum chloride and ultrasonically disperse them in deionized water. Control the molar ratio of lithium to cobalt to be 1.032. After ultrasonication for 30min, carry out a hydrothermal reaction at 220℃ for 7h. After the reaction, centrifuge and wash with water, then filter and dry to obtain carbon fiber supported MOFs-LiCo. 1-X Al X O2 three-dimensional porous composite material.

[0033] Figure 1 The carbon fiber-supported MOFs-LiCo prepared in this embodiment 1-X Al X A schematic diagram illustrating the preparation principle of O2 three-dimensional porous composite materials. Figure 2 This is the MOFs-LiCo synthesized in this embodiment. 1-X Al X XRD patterns of O2 / CFs, from Figure 2 It can be seen from this that Figure 2 The main diffraction peaks were those of LiCoO2, with no other impurities. Figure 3 This embodiment synthesizes MOFs-LiCo. 1- X Al X TEM images of O2 / CFs, by Figure 3 It can be seen that the synthesized MOFs have a cubic structure and are uniformly dispersed on the carbon fiber support. Figure 3 MOFs-LiCo 1-X Al X The O2 / RCF sTEM images show that LiCoO2 nanoclusters are dispersed and stacked within the MOF material. The MOFs confine and protect these LiCoO2 nanoclusters, and their flexible mechanical properties effectively mitigate the strain caused by the volume expansion of the transition metal. Simultaneously, lithium cobalt oxide (Aladdin) and the lithium cobalt oxide from Example 1 were purchased and compared in cycle rate performance testing. The results are as follows... Figure 4 As shown ( Figure 4In the examples, LiCoO2 is purchased lithium cobalt oxide, MOFs-LiCoO2 / cfs is the product prepared in Example 1, and MOFs-LiCoO2 is the product prepared in Comparative Example 1. Obviously, the prepared lithium cobalt oxide material has significantly improved cycle and rate performance compared with the purchased commercial lithium cobalt oxide material. This is due to: i) the MOFs structure effectively alleviates the strain caused by the volume expansion of the transition metal; ii) the abundant mesoporous structure is conducive to lithium electron transport and improves the kinetic performance of lithium ions during charging and discharging; iii) carbon nanofibers or graphene carbon materials with excellent conductivity can achieve high efficiency in lithium ion and electron conduction.

[0034] Example 2

[0035] A method for preparing a carbon-supported composite cathode material includes the following steps:

[0036] (1) First, 2g of cobalt nitrate, 25.3g of 2-methylimidazole and 5g of graphene oxide (RGO) (purchased by Aladdin) were ultrasonically dispersed in 15mL of methanol solution. Then, the three solutions were mixed and stirred at a stirring rate of 35r / min. After reacting for 12h, the stirring was turned off and the mixture was allowed to stand for 5min. A purplish-black precipitate was observed. The product was filtered, washed with water and dried in a vacuum oven at 90℃ to obtain graphene oxide-supported MOFs (MOFs / RGO).

[0037] (2) Take 5g of the prepared MOFs / RGO, 6.28g of lithium carbonate and 0.05g of aluminum chloride and ultrasonically disperse them in deionized water. Control the molar ratio of lithium to cobalt to be 1.033. After ultrasonication for 30min, carry out hydrothermal reaction at 220℃ for 7h. After the reaction, centrifuge, wash with water, filter and dry to obtain graphene oxide-supported MOFs-LiCo. 1-X Al X O2 three-dimensional porous composite material.

[0038] Example 3

[0039] A method for preparing a carbon-supported composite cathode material includes the following steps:

[0040] (1) First, 4g of cobalt nitrate, 27.8g of 2-methylimidazole and 6.5g of graphene oxide (RGO) (purchased by Aladdin) were ultrasonically dispersed in 15mL of methanol solution. Then, the three solutions were mixed and stirred at a stirring rate of 35r / min. After reacting for 12h, the stirring was turned off and the mixture was allowed to stand for 5min. A purplish-black precipitate was observed. The product was filtered, washed with water and dried in a vacuum oven at 90℃ to obtain graphene oxide-supported MOFs (MOFs / RGO).

[0041] (2) Take 6g of the prepared MOFs / RGO, 6.28g of lithium carbonate and 0.04g of lanthanum nitrate, and ultrasonically disperse them in deionized water. Control the molar ratio of lithium to cobalt to be 1.035. After ultrasonication for 30min, carry out a hydrothermal reaction at 240℃ for 5h. After the reaction, centrifuge, wash with water, filter and dry to obtain graphene oxide-supported MOFs-LiCo. 1-X La X O2 three-dimensional porous composite material.

[0042] Example 4

[0043] A method for preparing a carbon-supported composite cathode material includes the following steps:

[0044] (3) First, 4g of cobalt nitrate, 27.8g of 2-methylimidazole and 6.5g of graphene oxide (RGO) (purchased by Aladdin) were ultrasonically dispersed in 15mL of methanol solution. Then, the three solutions were mixed and stirred at a stirring rate of 35r / min. After reacting for 12h, the stirring was turned off and the mixture was allowed to stand for 5min. A purplish-black precipitate was observed. The product was filtered, washed with water and dried in a vacuum oven at 90℃ to obtain graphene oxide-supported MOFs (MOFs / RGO).

[0045] (4) Take 6g of the prepared MOFs / RGO, 6.28g of lithium carbonate and 0.04g of lanthanum nitrate, and ultrasonically disperse them in deionized water. Control the molar ratio of lithium to cobalt to be 1.034. After ultrasonication for 30min, carry out a hydrothermal reaction at 240℃ for 5h. After the reaction, centrifuge, wash with water, filter and dry to obtain graphene oxide-supported MOFs-LiCo. 1-X La X O2 three-dimensional porous composite material.

[0046] Comparative Example 1

[0047] A method for preparing a composite cathode material includes the following steps:

[0048] (1) First, 2g of cobalt nitrate and 25.3g of 2-methylimidazole were ultrasonically dispersed in 15mL of methanol solution. Then, the two ultrasonically dispersed solutions were mixed together, and the stirring was turned on at a rate of 35r / min. After reacting for 12h, the stirring was turned off and the mixture was allowed to stand for 5min. A purple precipitate was observed. The product was filtered, washed with water, and dried in a vacuum oven at 90℃ to obtain MOFs.

[0049] (2) Take 5g of the prepared MOFs, 6.28g of lithium carbonate and 0.05g of aluminum chloride and ultrasonically disperse them in deionized water. Control the molar ratio of lithium to cobalt to be 1.032. After ultrasonication for 30min, carry out hydrothermal reaction at 220℃ for 7h. After the reaction, centrifuge, wash with water, filter and dry to obtain MOFs-LiCo. 1-X Al X O2 three-dimensional porous composite material.

[0050] Comparative Example 2

[0051] Compared with Example 1, Comparative Example 2 did not have a MOF framework.

[0052] 2g of cobalt nitrate, 5g of carbon fiber (CFs), 6.28g of lithium carbonate, and 0.05g of aluminum chloride were ultrasonically dispersed in deionized water, with the molar ratio of lithium to cobalt controlled at 1.032. After ultrasonication for 30 min, a hydrothermal reaction was carried out at 220℃ for 7 h. After the reaction, the mixture was centrifuged, washed with water, filtered, and dried to obtain carbon fiber-supported LiCo. 1-X Al X O2 / CFs composite material.

[0053] The MOFs-LiCo obtained in Comparative Example 1 1-X Al X The O2 three-dimensional porous composite material underwent cycle and rate performance testing, and the test results are as follows: Figure 4 As shown ( Figure 4 In the text, LiCoO2 is purchased lithium cobalt oxide, MOFs-LiCoO2 / cfs is the product prepared in Example 1, and MOFs-LiCoO2 is the product prepared in Comparative Example 1. It can be seen that when there is no MOFs framework, the cycle rate performance of the material decreases significantly. The reason is that: i) the MOFs structure effectively alleviates the strain caused by the volume expansion of the transition metal; ii) the abundant mesoporous structure is conducive to lithium electron transport and improves the kinetic performance of lithium ions during charging and discharging; iii) carbon nanofibers or graphene carbon materials with excellent conductivity can achieve high efficiency in the conduction of lithium ions and electrons.

[0054] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a carbon-supported composite cathode material, characterized in that, Includes the following steps: (1) Mix the first solvent, cobalt source, organic ligand, and carbon material, and control the molar ratio of cobalt to organic ligand to be 1.5:(2-5) to obtain the first reaction system; control the first reaction system to react and obtain carbon-supported MOFs, i.e. MOFs / C; (2) mixing MOFs / C with a lithium source, an additive and a second solvent, controlling the molar ratio of lithium element to cobalt element in MOFs / C to be (1.01-1.05):1, to obtain a second reaction system; subjecting the second reaction system to a hydrothermal reaction at a temperature of 200-300°C for a reaction time of 5-10 h, to obtain a carbon-supported composite positive electrode material, namely MOFs-LiCo 1-x M x O2 / C, wherein M is one or more of aluminum, nickel, niobium, magnesium, lanthanum, zirconium, manganese and molybdenum, and 0<x≤0.1; the additive is one or more of aluminum chloride, nickel sulfate, niobium oxalate, magnesium chloride, lanthanum nitrate, zirconium chloride and manganese chloride.

2. The method for preparing the carbon-supported composite cathode material according to claim 1, characterized in that, Step (1) The preparation method of the first reaction system is as follows: First, the cobalt source, organic ligand and carbon material are dispersed in the first solvent to obtain the cobalt source dispersion system, the organic ligand dispersion system and the carbon material dispersion system. Then, the cobalt source dispersion system, the organic ligand dispersion system, and the carbon material dispersion system are mixed into a homogeneous dispersion system to obtain the first reaction system.

3. The method for preparing the carbon-supported composite cathode material according to claim 1, characterized in that, In step (1): the cobalt source is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate; the organic ligand is methylimidazole; and the carbon material is one or more of carbon fiber or graphene oxide.

4. The method for preparing the carbon-supported composite cathode material according to claim 1, characterized in that, Step (1) The reaction temperature of the first reaction system is 25-35℃ and the reaction time is 4-8h.

5. The method for preparing the carbon-supported composite cathode material according to any one of claims 1-4, characterized in that, In step (2): the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, and lithium nitrate.

6. The method for preparing the carbon-supported composite cathode material according to any one of claims 1-4, characterized in that, Step (2) also includes solid-liquid separation of the second reaction system after the reaction is completed to obtain a wet material, which is then dried at 90℃-120℃ for 4-12 hours to finally obtain MOFs-LiCo. 1-x M x O2 / C, 0 <x≤0.1。

Citation Information

Patent Citations

  • Sandwich-structure ternary nickel cobaltate lithium ion battery negative electrode material and preparation method thereof

    CN109841812A

  • MOFs derivative coated NCM ternary positive electrode material and preparation method thereof

    CN110224129A